Associations between fibrinogen levels and the risk of cardiovascular disease and all-cause death: a cohort study from the Chin-Shan community in Taiwan. Issue 4 (1st April 2022) - Hsieh, Cheng-Tzu; Chien, Kuo-Liong; Hsu, Hsiu-Ching; Lin, Hung-Ju; Su, Ta-Chen; Chen, Ming-Fong; Lee, Yuan-Teh
Abstract : Objectives: Although several studies have investigated the association between fibrinogen level and the risk of cardiovascular disease (CVD), few studies have been conducted in Asia. Setting: We conducted a community-based prospective cohort study in the Chin-Shan community, Taiwan. Participants: A total of 2222 participants (54.6±11.9 years, 53.4% women, and 22.4 years of follow-up) who underwent plasma fibrinogen measurements and were without CVD at baseline were recruited, among which 735 participants with available C reactive protein (CRP) were included in the joint analysis of the association of fibrinogen and CRP levels with the risk of CVD. Primary and secondary outcome measures: Fibrinogen and CRP levels were measured by clotting and high-sensitivity immunoturbidimetric assays, respectively. The study outcomes were CVD events and all-cause death. Our definition of CVD included both coronary artery disease (CAD) and stroke cases. Cox proportional hazards regression models were used to estimate the HRs and 95% CIs. Results: Compared with the lowest quartile, participants with higher fibrinogen levels tended to have a higher risk of CAD (adjusted HR for the highest quartile=1.48 (95% CI 0.90 to 2.44); test for trend p = 0.037) regardless of CRP level (adjusted HR=2.12 (95% CI 1.24 to 3.63) and 2.17 (95% CI 1.06 to 4.44) for high fibrinogen/low CRP and high fibrinogen/high CRP, respectively). The association was not observed for stroke (adjusted HR for the highest quartile=0.99 (95% CI 0.62 to 1.60); test for trend p = 0.99) and was only observed for all-cause death among participants <65 years of age (adjusted HR for the highest quartile=1.47 (95% CI 1.11 to 1.95); test for trend p = 0.004). Conclusions: Fibrinogen may be a potential risk factor for CAD but not for stroke. Further studies are necessary to clarify the differences in the role of fibrinogen levels on the risk of CVD between Asian and Western countries.